The Hubungan Beberapa Faktor Produksi Terhadap Peningkatan Produksi Telur Itik Di Kampung Isano Mbias Distrik Tanah Miring Kabupaten Merauke - Denvy Meidian Daoed (Faculty of Agriculture, Musamus University, 2024)
The purpose of this study were research is to analysis the relationship of several factors of production to the increased of duck eggs. The method of this research used was Observation, Questionnaires, Interviews,with a sample of 15 breeders. Were data analyzed descriptively tabulated and discussed. The results of thase factor of production is really influence on eggs production and average annual production increase and decrease of the duck faemers incomein the village Isano Mbias Tanah Miring District in Merauke Regency include small classification.